Legal Review of Regional Institutional Arrangements in the Provincial Government of West Sulawesi - Moh. Aqib Razak; Abdul Razak; Zulkifly Aspan (LEGAL BRIEF, 2021)
This study aims to determine and analyze the juridical urgency of structuring regional institutions and how the performance impact on the Provincial Government of West Sulawesi. This research was conducted in Mamuju Regency, West Sulawesi Province at the Office of the Governor of West Sulawesi Province, especially at the Organizational Bureau and the Legal Bureau of the Regional Secretariat of West Sulawesi Province. In this study, the author uses a normative research method, which focuses on written studies, namely, legislation, court decisions, legal theory, legal principles, legal principles, and can be in the form of scientific works of legal scholars (doctrine). The legal materials are analyzed using a statutory approach and a conceptual approach in order to obtain a systematic picture which is then further studied normatively using qualitative analysis techniques and then describes them according to the problem and then draws conclusions to determine the results. The results of the study show that: (1) Since the issuance of Permendagri No. 56 of 2019, the Provincial Government of West Sulawesi has made institutional arrangements for regional apparatus through Pergub No. 32 of 2020, the arrangement has merged the People's Welfare Bureau, and formed a new regional work unit, namely the Goods and Services Bureau and has changed the name of the Governance Bureau to the Government and People's Welfare Bureau. (2) In the arrangement of regional institutions of the West Sulawesi Provincial Government, As a result of this, the mandatory government affairs related to the land sector cannot be carried out because the Section has been merged and does not have an agency that oversees it.